Pembuatan Sistem Kendali Navigasi Wahana Selam Nir Awak Auv (Autonomous Underwater Vehicle) - Muhammad Tadjuddin (Jurnal Teknik Mesin Unsyiah, 2013)
Marine observation and research activities require a suitable transportation means that has an ability to bring necessary equipment for data collection and observation into the sea. One of the means that has the ability is AUV (Autonomous Underwater Vehicle), an electric powered underwater vehicle. The vehicle does not require cable connection from the surface and has an ability to move to global positions according to programmable trajectory installed in a microcontroller and other navigation equipment. The control system of the AUV trajectory is programmed in the microcontroller. The navigation equipment consists of integrated sensor. The main sensor used is global positioning sensor, digital compass, pressure sensor, and 3-axys gyroscopes. The main focus of this paper is the design and application of the control system for an underwater survey vehicle that has an ability to bring necessary equipment for observation of coastal area. The vehicle moves from an observation point to another according to GPS assisted programmed data. The control system consists of the thruster system, the depth control system, the positioning system and compass system. The design and algorithm for the control system is proposed.